Propriedade Intelectual e Apropriabilidade em Universidades Federais: Estudo Multicaso no Estado de Minas Gerais - André Siqueira Rennó (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2018)
The aim of this study was to investigate the mechanisms of knowledge appropriation in three universities in the State of Minas Gerais (Ufla, UFV and UFMG). A multicases study of qualitative and exploratory nature was conduct, based on bibliographical research and interviews with semi-structured script. The study proposes a Framework of Intellectual Property and Appropriability in Universities. The mechanisms identified were patent applications, software registers, cultivars registers, marks registers, other complementary mechanisms were: network formation, incubator of technology-based companies, Technology Park, partnerships between universities and companies, public cooperation partnerships. The study concludes that the University Offices of Technology Transfer (UOTT) still need to go through a set of stages. Some UOTT do not have members specialized in marketing skills, crucial for the success of technology transfer. This research finds a reality of universities that produce technologies, but little can promote these technologies and return them to society.